Strategies for Sustainable Land Management in the East African Highlands: Conclusions and Implications - Pender, John L.; Place, Frank; Ehui, Simeon (International Food Policy Research Institute, 2006)
The studies in this book sought to understand the factors affecting rural households’ choice of income strategies and land management practices and the implications of these decisions and of policy- and program-relevant factors for agricultural production, household welfare, and land degradation. We noted at the outset that the factors influencing these decisions and outcomes are many and complex and that their effects may be very context-dependent in a region as diverse as the East African highlands. The findings in the preceding chapters amply support this hypothesis.